2000
DOI: 10.1086/302833
|View full text |Cite
|
Sign up to set email alerts
|

Familial Posterior Fossa Brain Tumors of Infancy Secondary to Germline Mutation of the hSNF5 Gene

Abstract: We have identified a family afflicted over multiple generations with posterior fossa tumors of infancy, including central nervous system (CNS) malignant rhabdoid tumor (a subset of primitive neuroectodermal tumors, or PNET) and choroid plexus carcinoma. Various hereditary tumor syndromes, including Li-Fraumeni syndrome, Gorlin syndrome, and Turcot syndrome, have been linked to increased risk of developing CNS PNETs and choroid plexus tumors. Malignant rhabdoid tumors of the CNS and kidney show loss of heterozy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
87
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(97 citation statements)
references
References 14 publications
6
87
0
4
Order By: Relevance
“…This study thus documents the inheritance of a germline INI1-mutation that predisposes to the development of MBTs at young age in three subsequent generations of a family. Inheritance of an INI1-mutation via asymptomatic carriers has been reported before in two other families with childhood brain tumours (Taylor et al, 2000;Janson et al, 2006). Although the analyses of the latter families suggested that the asymptomatic transmission of the INI1-mutation exclusively occurred via female carriers, it is clear from our family that the transmission can as well take place via healthy male carriers.…”
Section: Discussion Inheritance Of the Ini1-mutationsupporting
confidence: 59%
See 3 more Smart Citations
“…This study thus documents the inheritance of a germline INI1-mutation that predisposes to the development of MBTs at young age in three subsequent generations of a family. Inheritance of an INI1-mutation via asymptomatic carriers has been reported before in two other families with childhood brain tumours (Taylor et al, 2000;Janson et al, 2006). Although the analyses of the latter families suggested that the asymptomatic transmission of the INI1-mutation exclusively occurred via female carriers, it is clear from our family that the transmission can as well take place via healthy male carriers.…”
Section: Discussion Inheritance Of the Ini1-mutationsupporting
confidence: 59%
“…Given the small number of splice site mutations in malignant rhabdoid tumours reported to date (Biegel, 2006), it is interesting to note that our family and one other multigeneration family with RTPS (Taylor et al, 2000) demonstrate an INI1 mutation at a splice site, raising the possibility that carriers of such a mutation may be less likely to be affected. In case of our family, there is the additional possibility that in the brain of the unaffected carriers alternative splicing of the INI1-mutant allele transcript, leading to absence of INI1 protein in the brain tumours of the patients, does not occur.…”
Section: Nf2 Rearrangement In the Tumours Of Patient Iii-1mentioning
confidence: 89%
See 2 more Smart Citations
“…SNF5 mutations are underlying familial cancers in which one SNF5 allele carries a germ-line mutation and the other allele is lost during tumorigenesis (Versteege et al 1998;Sevenet et al 1999;Taylor et al 2000). The tumor-suppressive effect of SNF5 is evident from the fact that reintroduction of SNF5 into SNF5-mutant tumor cells mediates cell cycle arrest (Betz et al 2002;Reincke et al 2003) and from mouse models demonstrating Snf5 as a haploinsufficient tumor-suppressor gene (Klochendler-Yeivin et al 2000;Roberts et al 2000), complete loss of which causes mice to succumb early in life to aggressive lymphomas or rhabdoid tumors (Roberts et al 2002).…”
Section: Messing Around With Nucleosomesmentioning
confidence: 99%